Therapy efficacy in multiple myeloma patients received autologous stem cells transplantation as first line therapy - Ye. I. Darskaya (Onkogematologiâ, 2014)
Therapy results of 91 patients with newly diagnosed multiple myeloma who received autologous hematopoietic stem cells transplantation are presented. According to our data, survival depends on the preransplant response and the amount of transplantations. 5-years progressionfree survival in patients, achieved pre-transplant complete or almost complete remission and received one auto-HSCT was 40 % compared with 18 % in patients who achieved only a partial response (p = 0.07). 10-years overall survival in patients received tandem auto-HSCT was 40 % compared with 20 % in patients after one auto-HSCT. Statistically significant differences in 5-years progression-free survival (34 % after tandem auto-HSCT vs. 22 % after one auto-HSCT; p = 0.004) also were revealed.